The Effectiveness of Sublingual Allergen-Specific Immunotherapy in Children with Allergic Rhinitis - M.P. Prokhorova (Zaslavsky O.Yu., 2015)
The article analyses the effectiveness of sublingual allergen-specific immunotherapy with sublingual house dust mite and pollen allergens (early and late spring and autumn grass mixture) in patients with seasonal allergic rhinitis, perennial allergic rhinitis and perennial allergic rhinitis with bronchial asthma with mild persistent course, bronchial asthma with moderate persistent course. The estimation of the dynamics of cellular, humoral and local immunity has been carried out before and after treatment with sublingual allergens. The influence of sublingual allergen-specific immunotherapy on the allergic eosinophilic inflammation is shown.